2021
DOI: 10.1182/blood.2021011707
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of nuclear m6A reader YTHDC1 in leukemogenesis by regulating MCM complex–mediated DNA replication

Abstract: YTHDC1 has distinct functions as a nuclear N6-methyladenosine (m6A) reader in regulating RNA metabolism. Here we show that YTHDC1 is overexpressed in Acute Myeloid Leukemia (AML) and that it is required for proliferation and survival of human AML cells. Genetic deletion of Ythdc1 markedly blocks AML development and maintenance as well as self-renewal of leukemia stem cells (LSCs) in vivo in mice. We find that Ythdc1 is also required for normal hematopoiesis and hematopoietic stem/progenitor cell (HSPC) mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 60 publications
3
68
0
Order By: Relevance
“…Furthermore, repression of YTHDF2 increased global m 6 A methylation levels, decreased Tnfrsf1b mRNA and protein expression levels and substantially suppressed the t(8; 21) AML cell proliferation ( Chen et al, 2021a ). According to the recent research conducted by Sheng and others, YTHDC1 is highly expressed in AML and regulates leukemogenesis by MCM4, which is a critical regulator of DNA replication ( Sheng et al, 2021 ). In another recent study, the data suggested that YTHDC1 is essential for AML cell survival, differentiation, and leukemogenesis.…”
Section: A Regulators-guided Epigenetic Modification In Cancersmentioning
confidence: 99%
“…Furthermore, repression of YTHDF2 increased global m 6 A methylation levels, decreased Tnfrsf1b mRNA and protein expression levels and substantially suppressed the t(8; 21) AML cell proliferation ( Chen et al, 2021a ). According to the recent research conducted by Sheng and others, YTHDC1 is highly expressed in AML and regulates leukemogenesis by MCM4, which is a critical regulator of DNA replication ( Sheng et al, 2021 ). In another recent study, the data suggested that YTHDC1 is essential for AML cell survival, differentiation, and leukemogenesis.…”
Section: A Regulators-guided Epigenetic Modification In Cancersmentioning
confidence: 99%
“…Thus, this study emphasizes the importance of YTHDF2 in the long-term maintenance of HSCs expansion. Apart from YTHDC2, another study [ 108 ] identified that YTHDC1 is also essential for maintaining the normal hematopoiesis and functional development of HSPCs in vivo. In an experiment on three mouse models, i.e., Ythdc1 fl/+ (WT), Ythdc1 fl/+ Mx1Cre ( Ythdc1 HET), and Ythdc1 fl/fl Mx1Cre ( Ythdc1 KO), whole blood cells as well as mature cells (e.g., myeloid, B cells, and T cells) in the serum of Ythdc1 KO mice were markedly reduced, and all mice died within three weeks.…”
Section: M 6 a Methylation Modification And Normal Hematopoietic Regulationmentioning
confidence: 99%
“…In addition, m 6 A exerts an important effect in AML progression, as it enhances the self-renewal capacity of AML cells. A recent study presented by Sheng’s group [ 108 ] found that YTHDC1, a nuclear m 6 A reader, is highly expressed in AML and that it contributes to the maintenance of AML cell proliferation and progression; knockdown of the YTHDC1 gene significantly blocked the proliferation of primary AML cells via modulating MCM complex-mediated DNA replication, as well as the self-renewal of LSCs in vivo in mice, thus achieving control of leukemogenesis. Collectively, this finding highlights the unique oncogenic mechanism of the m 6 A modifier YTHDC1 in AML.…”
Section: M 6 a Methylation Modifications And Hematological Malignanciesmentioning
confidence: 99%
“…nYACs play a crucial role in maintaining the stability of the target mRNA MYC, which is directly regulated by YTHDC1 in an m 6 A-dependent pathway, by preventing RNA degradation by the polyA tail exosome targeting complex (PAXT) ( 106 ). In addition to proliferation and colony formation, YTHDC1 also accounts for LSC self-renewal by enhancing the stability of minichromosome maintenance 4 (MCM4), which contributes to DNA replication ( 107 ). IGF2BP1 expressed in AML cells promotes leukemogenesis and proliferation and maintains the stemness of leukemia cells by regulating HOXB4, MYB, and ALDH1A1, which are LSC phenotype-associated transcriptional and metabolic factors.…”
Section: M 6 a Modification In Lscs And The Timementioning
confidence: 99%